Korupsi dan Pengaruh Kekuasaan Partai Politik (Follow The Money and Asset Recovery) - Hartanto Hartanto; Edy Chrisjanto; Murdomo Murdomo (Universitas Wahid Hasyim Semarang, 2024)
Corruption can be defined as an extraordinary crime. The consequences of corruption crimes can damage democratic values, morals (local wisdom), harm the country's finances and/or economy, and violate the social and economic rights of the community. Agencies responsible for investigating and prosecuting criminal acts of corruption include the police, prosecutor's office, and the Corruption Eradication Commission. Corruption is defined as the actions of those in positions of authority, including politicians and civil servants, who enrich themselves illegally and unfairly, abusing the power entrusted to them by society. Corruption is defined as the misappropriation of state or government funds (including those of companies, organizations, and foundations) for personal or other individuals' interests. It is imperative that law enforcement agencies prioritize focus, prevention, and strengthening. The research method employed is a legal and doctrinal approach, which examines secondary data. The author concludes that corruption persists and that the integrity of law enforcement officers is questionable. To eradicate corruption, it is necessary to re-focus on methods such as